Laparoscopic Bipolar Coagulation of Hypogastric Artery in Postpartum Haemorrhage: A Case Report. (6th September 2011) - Panuccio, Enrico; Volpi, Eugenio; Ferrero, Annamaria; Sismondi, Piero
Abstract : Background . Postpartum haemorrhage (PPH) is a significant contributor to worldwide maternal morbidity and mortality. When PPH continues despite aggressive medical treatment, early consideration should be given to surgical intervention. Various surgical interventions may be used but conservative interventions are recommended primarily. Case . This case report describes laparoscopic coagulation of hypogastric artery technique in a patient with PPH. Conclusions . Laparoscopic ligature of the hypogastric artery for PPH treatment can be a valid alternative to laparotomy in patients with vaginal delivery.